g-Jitter Induced MHD Mixed Convection Flow of Nanofluids Past a Vertical Stretching Sheet - Noraihan Afiqah, Rawi; Nor Athirah, Mohd Zin; Abdul Rahman, Mohd Kasim; Sharidan, Shafie (AIP Publishing, 2015)
The unsteady two dimensional convective boundary layer flow of nanofluids past a vertical permeable stretching sheet associated with the effect of g-jitter is studied in this paper. Two different types of water based nanofluids are considered which are copper (Cu) and aluminium oxide (Al2O3). The governing boundary layer equations in the form of partial differential equations are transformed into nonlinear coupled ordinary differential equations and solved numerically using an implicit finite-difference scheme known as the Keller-box method. The effects of amplitude of modulation, frequency of oscillation and solid nanoparticle volume fraction parameters on the reduced skin friction and Nusselt number are presented and discussed. An excellent agreement was observed between the current and earlier published results for some special cases. Numerical results show that, the values of reduced skin friction increase with the increasing of solid nanoparticle volume fraction but produce the opposite behaviour for the values of heat transfer coefficient.